2004
DOI: 10.1038/sj.bjc.6601620
|View full text |Cite
|
Sign up to set email alerts
|

Reduced total energy expenditure and physical activity in cachectic patients with pancreatic cancer can be modulated by an energy and protein dense oral supplement enriched with n-3 fatty acids

Abstract: The aim of the study was to assess the total energy expenditure (TEE), resting energy expenditure (REE) and physical activity level (PAL) in home-living cachectic patients with advanced pancreatic cancer. The influence of an energy and protein dense oral supplement either enriched with or without the n-3 fatty acid eicosapentaenoic acid (EPA) and administered over an 8-week period was also determined. In total, 24 patients were studied at baseline. The total energy expenditure was measured using doubly labelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
248
0
12

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(270 citation statements)
references
References 26 publications
10
248
0
12
Order By: Relevance
“…From a patient perspective, weight loss is associated with psychosocial distress30, 31 whilst deteriorating physical function (e.g. performance status) is associated with reduced quality of life 32, 33. Based on our observations and supported by previous work, we propose that weight loss and physical function are favourable endpoints in cancer cachexia trials, being meaningful for both patients and oncologists.…”
Section: Discussionsupporting
confidence: 77%
“…From a patient perspective, weight loss is associated with psychosocial distress30, 31 whilst deteriorating physical function (e.g. performance status) is associated with reduced quality of life 32, 33. Based on our observations and supported by previous work, we propose that weight loss and physical function are favourable endpoints in cancer cachexia trials, being meaningful for both patients and oncologists.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, the tumour-induced inflammatory response might further reduce the daily activity. Physical activity is a major determinant of quality of life (Moses et al, 2004). The complete nutritional combination tested maintained activity compared with TB-CON mice.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial in pancreatic cancer patients, in which a fish oil-enriched product was tested against an isocaloric/isonitrogenous placebo, no differences between groups were found on either LBM or physical activity. However, when compared with baseline values, total energy expenditure, resting energy expenditure and physical activity level increased significantly in those randomised to the n-3 enriched supplement (Moses et al, 2004). Other studies on supplementation with EPA or fish oil, specifically in cancer patients, showed a net lean tissue mass gain (Fearon et al, 2003), an increase in total resting energy expenditure and physical activity, a decreased need for total parenteral nutrition (TPN) (Kenler et al, 1996) and an improved quality of life (Fearon et al, 2003;Burns et al, 2004).…”
mentioning
confidence: 98%
“…Dal Negro et al 15 reported increased number of steps after EAA supplementation in domiciliary severe COPD patients. Alternatively, a positive effect of n‐3 fatty acid enriched protein‐dense supplements could be implicated as in cachectic patients with pancreatic cancer n‐3 FA supplementation also increased physical activity level assessed by doubly labelled water independent of muscle mass 24. Next to exercise, n‐3 FA additionally stimulate the PGC‐1α‐PPARα/δ pathway in muscle resulting not only in enhanced muscle (fat) oxidative metabolism25 and decreased muscle fatigue, but also in enhanced conversion of peripheral kynurenine into kynurenic acid, which is unable to cross the blood–brain barrier 26.…”
Section: Discussionmentioning
confidence: 99%